Stewart's clinical removable partial prosthodontics, fourth edition - Phoenix, Rodney D.; Phoenix, Rodney D.; Cagna, David R. (Chicago : Quintessence Publishing Co, Inc., 2008)
The fourth edition of this classic prosthodontic textbook features a new chapter on implant-assisted removable partial dentures as well as a description of the Prosthodontic Diagnostic Index. As before, the text provides an overview of removable partial denture service in contemporary dental practice with an emphasis on clinical and design aspects. Clinical topics range from examination and treatment planning to mouth preparation and prosthesis placement. Common design philosophies are discussed, and a step-by-step method for partial denture design is presented. Also included are alternative removable partial denture therapies such as Swing Lock, dual path, and attachment-type prostheses. To facilitate visualization and understanding, the text is accompanied by numerous illustrations. Like those that came before it, this edition is intended to help the student, the general practitioner, and the specialist consistently provide high-quality prosthodontic treatment for their patients.
Stewart's clinical removable partial prosthodontics, fourth edition -- Table of Contents -- Preface -- Contributors -- Chapter 1: Introduction and Classification -- Chapter 2: Major Connectors, Minor Connectors, Rests, and Rest Seats -- Chapter 3: Direct Retainers, Indirect Retainers, and Tooth Replacements -- Chapter 4: Mechanical Principles Associated with Removable Partial Dentures -- Chapter 5: The First Diagnostic Appointment -- Chapter 6: The Second Diagnostic Appointment -- Chapter 7: Survey and Design -- Chapter 8: I-bar Removable Partial Dentures -- Chapter 9: Implant-Assisted Removable Partial Dentures -- Chapter 10: Mouth Preparation and Master Cast -- Chapter 11: Laboratory Procedures for Framework Construct -- Chapter 12: Fitting the Framework -- Chapter 13: Special Impression Procedures for Tooth-Tissue-Supported Removable Partial Dentures -- Chapter 14: Establishing Occlusal Relationships -- Chapter 15: Try-In and Completion of the Partial Denture -- Chapter 16: Delivering the Removable Partial Denture -- Chapter 17: Postinsertion Observations -- Chapter 18: Maintenance and Repair of Removable Partial Dentures -- Chapter 19: Interim,Transitional, and Treatment Prostheses -- Chapter 20: Other Forms of Removable Partial Dentures -- Chapter 21: Attachments for Removable Partial Dentures -- Index.
Includes bibliographical references and index.
Keywords: Denture, Partial, Removable